THE CORRELATION BETWEEN STUDENTS’ VOCABULARY ACHIEVEMENT AND THEIR SPEAKING ACHIEVEMENT AT SECOND SEMESTER STUDENTS’ OF ENGLISH DEPARTMENT IN HALU OLEO UNIVERSITY - Al Ikzan, La Ode; Nggawu, La Ode; Siam, Siam (Universitas Halu Oleo, 2020)
This study aims to measure the correlation between vocabulary achievements and speaking achievement at second semester students of English study program in Halu Oleo University. The design of the study was research deign or correlational design; the type of the study was quantitative approach. The problem of the study was, is there any correlation between vocabulary achievement and speaking achievement at second semester students of English study program in Halu Oleo University? The population of this research was the second semester students of English Department in Halu Oleo University in the academic year of 2018/2019 with a total number of 120 students. It was divided into two class they are A and B. There are 105 students taken as sample in this study by using purposive sampling technique. The instruments of this research are mid test score of vocabulary examination and basic speaking Examination. The result of calculation using SPSS 20 program found that, (r (105) = 0.459, p = 0.000) was also higher than r at 5% and 1% significant level. It could be concluded that alternative hypothesis (H1 table) stating that there is a significant positive correlation between vocabulary achievement and speaking achievement at second semester students of English Department in Halu Oleo University and null hypothesis rejected. Based on the research findings, it is shown that there is positive correlation between vocabulary achievement and speaking achievement at second semester students of English Department in Halu Oleo University. It means that students’ who had much vocabulary performed speaking better than the student who had lack of vocabulary.